P111 Procedural Experience, Training Opportunities And Attitudes Towards Intercostal Chest Drain Insertion: Variations Between Consultants, Trainees And Medical Sub-specialties. (10th November 2014) - Corcoran, JP; Hallifax, RJ; Talwar, A; Psallidas, I; Sykes, A; Rahman, NM
Abstract : Background and method: Intercostal chest drain (ICD) insertion has long been considered a core skill for the general physician to master. The NPSA alert in 2008 highlighted potential hazards associated with this procedure, whilst recent guidelines 1 advocate the use of thoracic ultrasound to reduce complications. These developments have occurred at a time when trainees report a growing lack of confidence in their clinical experience and procedural capabilities, alongside a decline in training opportunities 2 that might address the latter concern. Nonetheless, competence in ICD insertion remains a compulsory or highly desirable procedural skill to acquire on a number of UK specialty training curricula including that for general (internal) medicine. We carried out a survey of consultants and trainees who contribute to general medical services in hospitals across the Thames Valley region. This survey assessed factors including physicians' attitudes towards ICD insertion; prior and recent procedural experience; training opportunities; and clinical knowledge. Results: 90 clinicians (26 consultants; 41 registrars (ST3+); 23 core medical trainees (CT1/2)) responded to the survey. Most clinicians (94% of responses) felt that placing >5 ICDs was necessary to attain initial competence at the procedure; before continuing to place >5 ICDs on an annual basis in order to maintain that competence (78% of responses). However, only 17% of medical registrars surveyed reached this basic combined standard. Other key findings are summarised in Table 1. Conclusion: Our findings demonstrate a disparity between clinical reality and the expectations junior doctors and consultants have of the physician in training with regards to ICD competence. Most trainees cannot achieve the number of procedures they feel are required to attain independence, nor maintain that independence on an annual basis; whilst access to training in thoracic ultrasound is limited outside certain specialties. This inexperience is manifest in variable clinical understanding and procedural confidence. Consideration needs to be given as to how medical training programmes might address these issues, and whether ICD insertion is even a skill that all general physicians can maintain competence in performing in the modern clinical environment. References: Thorax 2010;65 Suppl 2:ii61–76 Clin Med 2013;13(5):434–9